2023
DOI: 10.1029/2023gl104325
|View full text |Cite
|
Sign up to set email alerts
|

Sink, Source or Something In‐Between? Net Effects of Precipitation on Aerosol Particle Populations

Théodore Khadir,
Ilona Riipinen,
Sini Talvinen
et al.

Abstract: Interactions between atmospheric aerosols, clouds, and precipitation impact Earth's radiative balance and air quality, yet remain poorly constrained. Precipitating clouds serve as major sinks for particulate matter, but recent studies suggest that precipitation may also act as a particle source. The magnitude of the sources versus sinks, particularly for cloud condensation nuclei (CCN) numbers, remain unquantified. This study analyzes multi‐year in situ observations from tropical and boreal forests, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…8b). Prior studies have observed both an increase and decrease in the number concentration of Aitken-mode particles with precipitation accumulated along air mass trajectories (Khadir et al, 2023;Tunved et al, 2012). During rapid boundary layer growth under CAO conditions, entrainment is also likely to play a role (Tornow et al, 2022).…”
Section: Scavenging By Precipitationmentioning
confidence: 95%
See 1 more Smart Citation
“…8b). Prior studies have observed both an increase and decrease in the number concentration of Aitken-mode particles with precipitation accumulated along air mass trajectories (Khadir et al, 2023;Tunved et al, 2012). During rapid boundary layer growth under CAO conditions, entrainment is also likely to play a role (Tornow et al, 2022).…”
Section: Scavenging By Precipitationmentioning
confidence: 95%
“…Since the removal of aerosol particles has been linked to precipitation that occurs locally at a specific site in addition to along a calculated trajectory (Khadir et al, 2023;Tunved et al, 2012), we also examined the relationship of aerosol number concentration to local precipitation accumulated within the previous 24 hours at Andenes (Fig. 8b-d).…”
Section: Scavenging By Precipitationmentioning
confidence: 99%
“…The central Amazon is one of the few continental places where the atmospheric aerosol population, along with aerosol-cloud interactions, approaches conditions without significant anthropogenic impacts during particular periods of the wet season (February to May) (Martin et al, 2010;Pöhlker et al, 2016Pöhlker et al, , 2018Andreae et al, 2022). Cloud and precipitation formation are directly linked to the concentration and properties of atmospheric aerosols, which greatly affects the hydrological cycle of the basin (Andreae et al, 2001;Andreae, 2007;Artaxo et al, 2022;Khadir et al, 2023). In the Amazon, biogenic emissions, such as organic gases and aerosols, combined with the high concentration of water vapor and intense solar radiation, result in an atmosphere particularly susceptible to different external forcings that may change its composition (Pöhlker et al, 2012;Carslaw et al, 2013;Artaxo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%